Efektivitas e-LKPD Interaktif dalam Mengasah Keterampilan Menulis Kreatif Peserta Didik Kelas VII pada Pembelajaran Daring - Tamsiruddin Tamsiruddin (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study aims to determine and describe the effectiveness of using worksheet interactive (e-LKPD) in honing students' creative writing skills (fantasy stories) in online learning. The research method used is descriptive method, which describes the results of learning to write fantasy stories and student responses in using interactive e-LKPD by online learning. Data Sources of the study is students of class VII.1 UPTD SMP Negeri 1 Parepare. The data are the divided into two parts, namely the results of writing fantasy stories with interactive e-LKPD and student response using interactive e-LKPDs in writing fantasy stories obtained from online questionnaires. The results of data analysis showed that the students' skills in writing fantasy stories showed an average score of 85.35 which was included in the good category. Students agree, even strongly agree that the use of interactive e-LKPD is effective in writing fantasy stories. In addition, students said that the interactive e-LKPD was suitable for use in online and face-to-face learning.